Psychology, art, and antifascism : Ernst Kris, E.H. Gombrich, and the politics of caricature - Rose, Louis (Yale University Press, 2016)
"In 1934, Viennese art historian and psychoanalyst Ernst Kris invited his mentee E. H. Gombrich to collaborate on a project that had implications for psychology and neuroscience, and foreshadowed their contributions to the Allied war effort. Their subject: caricature and its use and abuse in propaganda. Their collaboration was a seminal early effort to integrate science, the humanities, and political awareness. In this fascinating biographical and intellectual study, Louis Rose explores the content of Kris and Gombrich's project and its legacy"--